New approaches to the synthesis and exfoliation of polymer/functional graphene nanocomposites by miniemulsion polymerization - Etmimi, Hussein Mohamed (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.